AYURVEDA: THE SOUND OF HEALING FOR LIFESTYLE DISORDERS - Velhal Amol (International Journal of Applied Ayurved Research, 2018)
Life style disorders are the toll we are paying for our lifestyle now a day. Once, communicable diseases were the prime killers in human society. But, now the studies shows that 17 million people die prematurely every year as a result of the global epidemic of largely preventable diseases or life style diseases. This means we are the killers of ourselves. A lifestyle typically reflects the way a person lives. It also includes an individual’s attitude, values or worldview. In simple language lifestyle is a characteristic bundle of behaviors. In this article, I am mainly concerned with the various regimen of diet and dietetics principle, daily routine and other preventive measures of Ayurveda mentioned in the Ayurveda texts for the prevention of lifestyle disorders. The science of Ayurveda is designed to help us live in harmony with our environment. Part of living in harmony with one’s environment includes balanced use of the senses. So it is mandatory to develop a health oriented life style than to give deep concern about our works. According to Ayurvedic text, the three pillars of healthy and long life are: Aahara (proper diet), Nidra (proper sleep) and Bramhacharya (controlled sexuality). In the management of these lifestyle diseases, Ayurveda offers various regimens such as Dinacharya (daily regimen), Ritucharya (seasonal regimen), Sadvritta (ideal routines), and Acharya Rasayana (code of conduct). In short, Ayurvedic lifestyle promotes physical, mental as well as social health and ultimately leads to symptomatic improvement and improvement in the quality of life and thus help in the prevention and management of lifestyle disorders.